Public investment efficiency and sectoral economic growth in Pakistan - Ahmed, Qazi Masood; Ali, Syed Ammad (International Food Policy Research Institute, 2014)
This paper compares the effects of aggregate and sectoral public investments on sectoral private investment, output, and employment. We estimate the elasticities of private investment with respect to aggregate and sectoral public investments to find crowding-out or crowding-in phenomena in Pakistan. The study also reveals the changes in labor absorption or replacement due to additional capital and the effects on output. Our data covers eight sectors of the Pakistan economy and uses annual time series data from 1964 to 2011. This study uses vector autoregressive (VAR) techniques, as applied by Pereira (2000, 2001), which allows measuring the dynamic feedback effects among the variables.